قاعدة اعتبار المآلات وأثرها في الفتوى - د ا رسة تأصیلیّة تطبیقیّة - الهامل, إبراهیم (University of Eloued-جامعة الوادي, 2015)
This study is titled by: The base consideration results and it's impact in fatwa.It is also Looking at the extent of the base effect in fatwa. The study has two chapters. The first chapter is concerned with the theoretical side of both of the base considered results and fatwa, and the second one is for the impact of the base in scholars' fatwa weather the previous or the currentones. All of this through mentioning Models of their fatwas which is based on it or being a reason to change the fatwa. The study concluded that the most important result whish is based in the base of results continues to be used by the scholarsfrom the time of the Messenger of Allah 􀀀 to our time.
مذكرة ماستر
Keywords: قاعدة اعتبار المآلات / الفتوى /الفقهاء القدامى/ الفقهاء المعاصرین/تغیُّر الفتوى/; The rule of considering the consequences / Fatwa / Old jurists / Contemporary jurists / Changing the fatwa /